DESCRIPTION OF UNDERSTANDING MATHEMATICAL CONCEPTS ABILITY BASED ON BRAIN DOMINATION - Meike Wigati; Gunawan Gunawan; Lukmanul Akhsani; Jaka Wijaya Kusuma (Yayasan Education and Social Center, 2023)
One of the essential cognitive aspects of learning mathematics is the ability to understand concepts. This study describes the ability to understand students' mathematical concepts based on brain dominance. The type of research used is descriptive qualitative. The research subjects were high school students. The instruments used were tests, questionnaires, and interview guidelines. Data analysis techniques consist of data reduction, presentation, and conclusion. The results showed that students left brain dominant student has excellent mathematical concepts understanding ability, provide clear and detailed information, provide examples with different shapes or arrangements, use symbols other than numbers, and they are confident that they understand the concepts. Meanwhile, right-brain dominant students have a relatively good mathematical concepts understanding ability, tend to convey information randomly using their language, provide examples with similar shapes or arrangements, and must be more sure that they understand the concept